Endovenous Laser Application - Sroka, R.; Hemmerich, M.; Pongratz, T.; Siegrist, K.; Brons, J.; Linden, S.; Meier, R.; Schmedt, C.-G. (Phlebologie, 2013)
Introduction: Endovenous laser ablation is becoming a common procedure in clinical routine. Although technical improvements and certain laser parameters are available there is demand to improve the situation by developing feedback-systems, thus getting online information for the clinical outcome and preventing for under- and over-treatment.Methods: By means of Monte Carlo simulation the potential of detecting signals due to heat induced shrinkage of the vessel was investigated. Remission spectra of native and coagulated vein tissue were compared to identify potential parameters for signalling the physiological change of the tissue due to the heating process. A miniaturized temperature sensor was developed for intraluminal measurements during laser energy application.Results: Monte Carlo simulation shows that the detection of remitted light from the vessels wall is possible for small vessel calibres of less than 6 mm in diameter. Remission spectra of native compared to coagulated vein tissue differ. While native tissue relates more to the content of deoxy-hemoglobin, the spectra of coagulated tissue relates more to the oxy-hemoglobin state. Based on the principle of temperature dependent fluorescence emission a miniaturized sensor was developed which can be used in the light field of radial emitting fibres.Conclusion: Several optical changes for online-monitoring of signals during endovenous laser ablation showed potential to serve as feedback mechanism. Up to now, only the measurement of the endoluminal temperature could be realized. Further investigations are needed to find suitable technical realization to prevent for under- or overheating during endovenous laser ablation.
Keywords: Varicosis; laser; temperature; monitoring